Prediction of the relationship with the spouse based on wisdom and thought control strategies and the moderating role of the dimensions of family relationships and triangulation in married women - Rejali , Hoda; Yousefi , Zahra (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was aimed to predict the relationship with the spouse based on wisdom and thought control strategies with the moderating role of the dimensions of family relationships (relationship with one's family, relationship with the spouse's family) and triangulation among married women in Kashan. Method: The research method was descriptive and correlational, and the statistical population included all married women in Kashan. A sample of 210 married women was selected by the convenience sampling method from different areas of Kashan city. The research tools included Ardelt Wisdom Scales (2013), Wells and Davies (1994), Thought Control Strategies, Barnes & Olson (2004) Family Relationships, and Peasant and Yousefi Triangulation (2019). The data were analyzed by the Pearson correlation method and hierarchical regression analysis. Results: The results of Pearson correlation showed that all predictor and moderator variables have a significant correlation with the factor of relationship with the spouse (P